2002
DOI: 10.1021/ja0275921
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of an Isocyanate Functionalized Polyhedral Oligosilsesquioxane and the Subsequent Formation of an Organic−Inorganic Hybrid Polyurethane

Abstract: Organic-inorganic hybrids are an important class of new materials that offer improved thermal and mechanical properties over normal polymers. They may be produced by either the sol-gel route or through the use of inorganic compounds possessing reactive functional groups. Polyhedral oligosilsesquioxanes (POSS) are completely defined molecules of nanoscale dimensions that may be functionalized with reactive groups suitable for the synthesis of new organic-inorganic hybrids. Here we report the synthesis and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(119 citation statements)
references
References 23 publications
2
117
0
Order By: Relevance
“…POSS with one or more covalently bonded reactive groups is suitable for polymerization, grafting, surface bonding, blending and other transformations to build organic/inorganic hybrid materials at the molecular level. [9][10][11][12][13] POSS functionalized with groups such as hydrogen, 14 amine, 15 vinyl, 16 epoxy 17 and isocyanate 18 can be used as monomers or comonomers in typical polymerizations. One such POSS, hydrogen silsesquioxane (HSQ), has attracted increasing interest in scientific research and technological innovation.…”
Section: Introductionmentioning
confidence: 99%
“…POSS with one or more covalently bonded reactive groups is suitable for polymerization, grafting, surface bonding, blending and other transformations to build organic/inorganic hybrid materials at the molecular level. [9][10][11][12][13] POSS functionalized with groups such as hydrogen, 14 amine, 15 vinyl, 16 epoxy 17 and isocyanate 18 can be used as monomers or comonomers in typical polymerizations. One such POSS, hydrogen silsesquioxane (HSQ), has attracted increasing interest in scientific research and technological innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Neumann et al 55 first obtained POSS with eight -NCO groups, using hydrosilylation of octakis (dimethylsiloxy) octasilsesquioxane (Q 8 M 8 H ), as shown in Figure 9. As the crosslinking agent, Q 8 M 8 H reacted with poly (ethylene glycol) to form crosslinked polyurethane.…”
Section: Isocyanate-possmentioning
confidence: 99%
“…[18][19][20][21] The proton nuclear magnetic spectrum of POSS-OH is shown in Supplementary Figure S1a. The disappearance of the Si-H proton resonance peak at 4.72 p.p.m in proton nuclear magnetic resonance indicated that all eight corners of the POSS core were substituted with the hydroxyl group.…”
Section: Synthesis Of Star-shaped Poss-pclmentioning
confidence: 99%
“…Knight et al 18 reported that there was minimal weight loss for POSS-incorporated polyester PU films in the earlier stage, followed by a large mass loss at the later stage of in vitro degradation, and the hybrid films also exhibited excellent biocompatibility with no inflammatory responses. POSS-PU hybrids were reported [19][20][21] to possess improved properties, such as higher thermal stability, higher oxidative resistance and increased mechanical strength.…”
Section: Introductionmentioning
confidence: 99%